2018
DOI: 10.1111/jcal.12326
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between perceived problem‐solving skills and academic performance of novice learners in introductory programming courses

Abstract: Past research has shown that student problem‐solving skills may be used to determine student final exam performance. This study reports on the relationship between student perceived problem‐solving skills and academic performance in introductory programming, in formative and summative programming assessment tasks. We found that the more effective problem solvers achieved better final exam scores. There was no significant difference in formative assessment performances between effective and poor problem solvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 45 publications
1
19
0
1
Order By: Relevance
“…Students with higher problem-solving capacity, are also likely to score highly in final national exams (Veerasamy et al, 2018). The results from the studies conducted by Lian et al (2010), and Mukuka, Balimuttajjo, and Mutarutinya (2020) demonstrate a need for teachers to make use of the SOLO taxonomy, through an enhanced PBL environment, in assessing students' mathematical problem-solving abilities.…”
Section: Discussion and Implications Of The Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students with higher problem-solving capacity, are also likely to score highly in final national exams (Veerasamy et al, 2018). The results from the studies conducted by Lian et al (2010), and Mukuka, Balimuttajjo, and Mutarutinya (2020) demonstrate a need for teachers to make use of the SOLO taxonomy, through an enhanced PBL environment, in assessing students' mathematical problem-solving abilities.…”
Section: Discussion and Implications Of The Research Findingsmentioning
confidence: 99%
“…Teachers need to identify which competence is expected in each unit of the mathematics curriculum. In line with these expectations, teachers need to identify and categorise students' problemsolving abilities in line with the constructivist learning theory (Veerasamy et al, 2018).…”
Section: Discussion and Implications Of The Research Findingsmentioning
confidence: 99%
“…Perceived vs academic performance [55] Correlation among problem solving skill (PSS) and student performance has been measured in an experiment on 200 students from one semester in 2016 and Spearman's rank correlation coefficient technique is used for empirical validation This study found weak correlation among students' performance in formative and summative assessment tasks and PSS. However, assessing student PSS levels may help instructors to develop instructional interventions and assessment tasks and to improve student academic self-efficacy and problem solving and in learning programming.…”
Section: ) Students' Performance Analysismentioning
confidence: 99%
“…Various factors have been reviewed in studies [17] [55] to improve student academic self-efficacy and problem solving and in learning programming by applying Spearmans' rank correlation coefficient technique. It was identified in [55] that performance in formative assessment and problem-solvingskill are weakly correlated. These studies aim to discover correlation between various assessment method, student's participation and their final performance.…”
Section: ) Assessment Designmentioning
confidence: 99%
“…To measure the student learning progress most of the educators use formative assessment in order to ascertain the level of understanding or the learning difficulties and recommends remedial methods to improve student learning (Lawton et al 2012) (Heritage 2010) (Veerasamy et al 2019). Prerequisite factors are important in predicting student performance (Longi 2016)(Sharma and Shen 2018) (Csizér and Magid 2014).…”
Section: Related Workmentioning
confidence: 99%